2022
DOI: 10.1093/cercor/bhac159
|View full text |Cite
|
Sign up to set email alerts
|

Sleep loss disrupts the neural signature of successful learning

Abstract: Sleep supports memory consolidation as well as next-day learning. The influential Active Systems account of offline consolidation suggests that sleep-associated memory processing paves the way for new learning, but empirical evidence in support of this idea is scarce. Using a within-subjects (N = 30), crossover design, we assessed behavioural and electrophysiological indices of episodic encoding after a night of sleep or total sleep deprivation in healthy adults (aged 18-25 years), and investigated whether beh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…Screening questionnaires indicated that participants had no history of sleep, neurological or psychiatric disorders, were non-smokers and were not using any psychoactive medications. Following standard practices in our lab, participants were instructed to refrain from alcohol and caffeine for 24 hours before the start of the study (Ashton et al, 2019;Cairney, Lindsay, et al, 2018;Guttesen et al, 2022;Strachan et al, 2020). The Pittsburgh Sleep Quality Index (Buysse et al, 1989) indicated that all participants had a normal pattern of sleep in the month preceding the study.…”
Section: Participantsmentioning
confidence: 99%
“…Screening questionnaires indicated that participants had no history of sleep, neurological or psychiatric disorders, were non-smokers and were not using any psychoactive medications. Following standard practices in our lab, participants were instructed to refrain from alcohol and caffeine for 24 hours before the start of the study (Ashton et al, 2019;Cairney, Lindsay, et al, 2018;Guttesen et al, 2022;Strachan et al, 2020). The Pittsburgh Sleep Quality Index (Buysse et al, 1989) indicated that all participants had a normal pattern of sleep in the month preceding the study.…”
Section: Participantsmentioning
confidence: 99%
“…Based on the accumulating evidence that the functioning of the hippocampus and associated MTL areas are disrupted by sleep deprivation in humans and in animal models (Tudor et al, 2016;Guttensen et al, 2023), it would be surprising if we did not observe significant effects of sleep loss on memory. However, to understand what aspects of memory are, and are not, affected by sleep deprivation requires a deeper understanding of the role of the hippocampus in memory.…”
Section: Discussionmentioning
confidence: 79%